Satirical Language as a Representation of Love in The Novel Iki Ati Dudu Watu (A Stylistic Study) and Its Relevance to Javanese Language Learning - Ryan Ikhwan Khairi; Afendy Widayat (Piwulang: Jurnal Pendidikan Bahasa Jawa, 2026)
This study is grounded in the view that language in literary works functions not merely as a means of communication but as a medium of representation that constructs and gives meaning to experiences of love, which are often expressed indirectly through satire. The study aims to describe the forms of satirical language as representations of love and to explain their relevance to Javanese language learning at vocational high schools (SMK). The research employs a qualitative descriptive method, with data sources consisting of textual excerpts containing sarcasm, cynicism, irony, satire, antiphrasis, and innuendo. Data were collected through close reading and note-taking techniques, analyzed in stages of data condensation, categorization, tabulation, interpretation, and inference, and validated using semantic validity and intra- and interrater reliability. The findings reveal that satirical language in the novel represents five dimensions of love: brotherly love, maternal love, erotic love, self-love, and love of God, which function expressively, reflectively, critically, relationally, and aesthetically in constructing conflict and deepening characterization. The implications of this study enrich Javanese literary stylistics and can be integrated into Javanese language instruction at SMK to enhance students’ interpretative competence, sensitivity to implicit meaning, and character education grounded in cultural and spiritual values.